Size controllable single-crystalline Ni-rich cathodes for high-energy lithium-ion batteries. Issue 2 (19th October 2022) - Shi, Ji-Lei; Sheng, Hang; Meng, Xin-Hai; Zhang, Xu-Dong; Lei, Dan; Sun, Xiaorui; Pan, Hongyi; Wang, Junyang; Yu, Xiqian; Wang, Chunsheng; Li, Yangxing; Guo, Yu-Guo
ABSTRACT: A single-crystalline Ni-rich (SCNR) cathode with a large particle size can achieve higher energy density, and is safer, than polycrystalline counterparts. However, synthesizing large SCNR cathodes (>5 μm) without compromising electrochemical performance is very challenging due to the incompatibility between Ni-rich cathodes and high temperature calcination. Herein, we introduce Vegard's Slope as a guide for rationally selecting sintering aids, and we successfully synthesize size-controlled SCNR cathodes, the largest of which can be up to 10 μm. Comprehensive theoretical calculation and experimental characterization show that sintering aids continuously migrate to the particle surface, suppress sublattice oxygen release and reduce the surface energy of the typically exposed facets, which promotes grain boundary migration and elevates calcination critical temperature. The dense SCNR cathodes, fabricated by packing of different-sized SCNR cathode particles, achieve a highest electrode press density of 3.9 g cm −3 and a highest volumetric energy density of 3000 Wh L −1 . The pouch cell demonstrates a high energy density of 303 Wh kg −1, 730 Wh L −1 and 76% capacity retention after 1200 cycles. SCNR cathodes with an optimized particle size distribution can meet the requirements for both electric vehicles and portable devices. Furthermore, the principle for controlling the growth of SCNR particles can be widely applied when synthesizing other materials for Li-ion, Na-ion and K-ion batteries. Abstract : Controllable grain sizes in a wide range enable the single-crystalline Ni-rich cathode to break through the bottleneck of volumetric energy density, which makes it qualified to replace LiCoO2 and alleviate the cobalt crisis.